2013
DOI: 10.1159/000354541
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Added Fluvastatin to Standard-of-Care Treatment on Sustained Virological Response in Naïve Chronic Hepatitis C Patients Infected with Genotypes 1 and 3

Abstract: Objectives: The combination of pegylated interferon-α and ribavirin is a standard-of-care (SOC) treatment for chronic hepatitis C (CHC), and it achieves a sustained virological response (SVR) in 41-52% of genotype 1 and in 73-79% of genotype 3 patients. In a few clinical trials, the combination of fluvastatin and SOC increased the SVR in genotype 1 patients. Methods: This prospective study enrolled 179 naïve CHC patients. In the fluvastatin group patients received the combination of SOC and fluvastatin 80 mg d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In one analysis of patients with HCV 1-3 genotypes who received combination therapy with PEG-IFN/Rbv, the significant impact of statin use was only observed among the HCV G1 patients. [20] Similar findings were reported by Kurincic et al [21] Steatosis is a common histologic finding in patients infected by HCV G3, independently of the presence of fibrosis, diabetes, hepatic inflammation, ongoing alcohol abuse, higher body mass index and older age [22]. Indeed, steatosis in HCV G3 infected patients is not the result of overexpression of genes involved in lipogenesis.…”
Section: Editorialsupporting
confidence: 77%
“…In one analysis of patients with HCV 1-3 genotypes who received combination therapy with PEG-IFN/Rbv, the significant impact of statin use was only observed among the HCV G1 patients. [20] Similar findings were reported by Kurincic et al [21] Steatosis is a common histologic finding in patients infected by HCV G3, independently of the presence of fibrosis, diabetes, hepatic inflammation, ongoing alcohol abuse, higher body mass index and older age [22]. Indeed, steatosis in HCV G3 infected patients is not the result of overexpression of genes involved in lipogenesis.…”
Section: Editorialsupporting
confidence: 77%
“…This genotype variability has not yet been adequately studied, given the fact that most clinical studies to date have been conducted on patients infected with HCV genotype 1 [ (Kondo et al, 2012) (Kohjima et al, 2013)]. A recent prospective study investigating treatment efficacy of added FLV to PEG-IFN/RBV therapy in genotype 1 and genotype 3 patients reported no significant increase in SVR rates in the genotype 3 patient population, in contrast to genotype 1 patients with a high viral load, indicating that the antiviral efficacy of statins may indeed be genotype-dependent (Kurincic et al, 2014).…”
Section: Ii) Prospective Studiesmentioning
confidence: 99%
“…Most studies have analysed the effect of Fluvastatin on the virologic response, and the number of studies that analysed other statins is lower. There are studies that are potentiating the positive impact of Fluvastatin as an additional therapy of standard antiviral therapy over virologic response, especially for genotype 1, such as the study of Selic Kurincic et al, [31]. The study of Atsukawa et al, [32], showed the reduction of viral relapse in patients with genotype 1b, as well as the studies of Georgescu et al, [33], Sesaki et al, [34] and Kondo et al, [35].…”
Section: Discussionmentioning
confidence: 99%